The Routledge handbook of public health and the community - Fong, Ben Y. F.; Wong, Martin C. S. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
Community health is an emerging and growing discipline of public health and it focuses on the physical, social, and mental well-being of the people of specific districts. This interdisciplinary field brings together aspects of health care, economics, environment, and people interaction. This handbook is a comprehensive reference on public health for higher education students, scholars, practitioners, and policymakers of health care. There are five key thematic sections in the book: perspectives in public health; community health in practise; planning, built, and social environment and community health; digital and mobile health; and,towards sustainable health in the community. Each theme explores the leading research and trends. This book aims to help achieve the shared goal of healthier communities and quality of life for the residents. This collaborative work should be a very useful handbook to health professionals and government bodies in the planning of initiatives to improve population health, prevent chronic diseases, control infectious diseases and outbreaks, and prepare for natural disasters. This handbook integrates research and practise of public health in the community.
Keywords: Public health; Medical policy; BUSINESS & ECONOMICS / Insurance / Health; POLITICAL SCIENCE / Public Affairs & Administration